THE WAY OF COMUNICATION - Yayi, Sri (Fakultas Teknik Universitas Krisnadwipayana, 2016)
The way of comunication toward students junior high school in Eas Jakarta. The purpose of this study was to investigation the effect vocab, listening , speaking , reading, stucture toward students in SMP Pelita Tiga east Jakarta. There is an effect which significant the poor vocab, listening senten structure and speaking skill dificult to comunication. Data were colected by instrument in the from of objective.